Family Business Groups around the World: Financing Advantages, Control Motivations, and Organizational Choices - Masulis, Ronald W.; Pham, Peter Kien; Zein, Jason (Review of Financial Studies, 2011)
Using a dataset of 28,635 firms in 45 countries, this study investigates the motivations for family-controlled business groups. We provide new evidence consistent with the argument that particular group structures emerge not only to perpetuate control, but also to alleviate financing constraints at the country and firm levels. At the country level, family groups, especially those structured as pyramids, are more prevalent in markets with limited availability of capital. At the firm level, investment intensity is greater for firms held in pyramidal rather than in horizontal structures, reflecting the financing advantages of the former. Within a pyramid, internal equity funding, investment intensity, and firm value all increase down the ownership chain. However, group firm performance declines when dual-class shares and cross shareholdings are employed as additional control-enhancing mechanisms.